KARAKTERISTIK KINERJA TURBIN NEST-LIE PADA PROTOTIPE PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO - Wira Mastika, I Nyoman; Jasa, Lie; Manuaba, Ida Bagus Gede (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p2, 2020)
Water energy is energy that comes from water flow which is used to produce electrical energy by using a flow of water that flows to turn a turbine, then the turbine is connected to a generator. Micro-hydro power plants are usually built in areas that have the potential for generating electricity in a small capacity. The choice of location of a micro hydro power plant is largely determined by the potential for water fall or often called a waterfall. Parameters that can be changed to improve turbine efficiency are the shape of the turbine blade, turbine blade volume, nozzle angle, and nozzle position. The method used is the method of observation by observing and testing directly and the method of literature by studying the literature - literature from several references. Performance characteristics of nest-lie turbines produce higher torque values than triangular turbine blades. Nest-lie turbine produces a torque value of 0.0076 Nm at position 450 nozzle and nozzle angle 100. This shows that the nest-lie turbine has characteristics that are better than a triangular turbine blade.